An Immersed Interface Method for Axisymmetric Electrohydrodynamic Simulations in Stokes Flow (Communications in Computational Physics, 2018)
A numerical scheme based on the immersed interface method (IIM) is developedto simulate the dynamics of an axisymmetric viscous drop under an electric field.In this work, the IIM is used to solve both the fluid velocity field and the electric potentialfield. Detailed numerical studies on the numerical scheme show a second-orderconvergence. Moreover, our numerical scheme is validated by the good agreementwith previous analytical models [1, 31, 39], and numerical results from the boundaryintegral simulations [17]. Our method can be extended to Navier-Stokes fluid flowwith nonlinear inertia effects.